The Social Return on Investment in programs designed for young people living with a family member who experiences mental health challenges: study protocol - Reupert, Andrea Erika; Freeman, Nerelie Claire; Nandakumar, Nivedita; Hine, Rochelle; Cain, Rebecca; Foster, Kim (Frontiers in Public Health, 2025)
The purpose of this paper is to describe the protocol for the evaluation of programs offered by the Satellite Foundation, designed for, and with, children and young people aged between 8 and 25 years who have family members experiencing mental health challenges. To achieve this, the Social Return on Investment (SROI) method was chosen. SROI is an economic measurement tool used to apply a monetary value to socially situated outcomes. In this study, SROI will be used to provide a means of quantifying the social impact generated by various programs offered by the Satellite Foundation, a community-based mental health organisation. These programs are designed for children and young people who have a family member who experiences mental health challenges, with the aim to promote resilience, hope and connectedness. Given that traditional financial metrics often fail to capture societal benefits, SROI offers a systematic approach to measuring the economic and often intangible social outcomes of any given endeavour. This protocol will describe the SROI method, who the stakeholders are, and how they are engaged. The rationale for the monetisation of outcomes is shown. Other SROI steps are presented, including how impact was established, and the proposed method of calculating the SROI. The limitations and potential benefits of this economic measurement approach are also discussed.